Exogenous glucose oxidation during endurance exercise under low energy availability - Kojma, C.; Ishibashi, A.; Ebi, K.; Goto, K. (PLOS ONE, 2022)
The present study was conducted to determine the effect of endurance exercise under low energy availability (EA) on exogenous glucose oxidation during endurance exercise. Ten active males (21.4 ± 0.6 years, 170.4 ± 1.4 cm, 62.4 ± 1.5 kg, 21.5 ± 0.4 kg/m2) completed two trials, consisting of two consecutive days (days 1 and 2) of endurance training under low EA (19.9 ± 0.2 kcal/kg fat free mass [FFM]/day, LEA trial) or normal EA (46.4 ± 0.1 kcal/kg FFM/day, NEA trial). The order of these two trials was randomized with at least a 1-week interval between trials. As an endurance training, participants performed 60 min of treadmill running at 70% of maximal oxygen uptake () during two consecutive days (on days 1 and 2). On day 1, the endurance training was performed with consumed individually manipulated meals. During the endurance exercise on day 2, exogenous glucose oxidation was evaluated using 13C-labeled glucose, and respiratory gas samples were collected. In addition, blood glucose and lactate concentrations were measured immediately after exercise on day 2. Body composition, blood parameters, and resting respiratory gas variables were evaluated under overnight fasting on days 1 and 2. Body weight was significantly reduced in the LEA trial on day2 (day1: 61.8 ± 1.4 kg, day 2: 61.3 ± 1.4 kg, P < 0.001). There were no significant differences between trials in 13C excretion (P = 0.33) and area under the curve during the 60 min of exercise (LEA trial: 40.4 ± 3.1 mmol•60min, NEA trial: 40.4 ± 3.1 mmol•60min, P = 0.99). However, the respiratory exchange ratio (RER, LEA trial: 0.88 ± 0.01, NEA trial: 0.90 ± 0.01) and carbohydrate oxidation (LEA trial: 120.1 ± 8.8 g, NEA trial: 136.8 ± 8.6 g) during endurance exercise showed significantly lower values in the LEA trial than in the NEA trial (P = 0.01 for RER and carbohydrate oxidation). Serum insulin and total ketone body concentrations were significantly changed after a day of endurance training under low EA (P = 0.04 for insulin, P < 0.01 for total ketone). In conclusion, low EA during endurance exercise reduced systemic carbohydrate oxidation; however, exogenous glucose oxidation (evaluated by 13C excretion) remained unchanged during exercise under low EA